Enhancing Preliminary Database of Volcanic Debris Avalanches in Indonesia: A Focus on Morphological Type and Geological Data - Malawani, Mukhamad Ngainul; Hamdani, Agus Jaiz; Abidin, Imam Alief Naufal; Estiono, Meru Sigit; Pratiwi, Dinda; Lavigne, Franck; Handayani, Tiara; Suhendro, Indranova (Indonesian Journal on Geoscience, 2026)
Indonesia has many cases of volcanic debris avalanche (VDA), which is fifty-four events from the inventory conducted by MacLeod (1989). However, data on the characteristics of VDA provided is limited, therefore it is necessary to develop detailed information related to these fifty-four cases. This study focuses on morphological and geological inventory of the VDA in Indonesia. Using the DEM database, morphological features were analyzed and four classes were determined, namely (1) volcanoes with horseshoe-shaped scar only; (2) volcanoes with no horseshoe-shaped scar, but has DAD (debris avalanche deposit); (3) volcanoes with no horseshoe-shaped scar, and no DAD; and (4) volcanoes with horseshoe-shaped scar and with DAD. Most of the volcanoes that have VDA are clustered in the first class. From the geological map, three main main pieces of information can be obtained: relative age, rocks/materials, and structure. Of fifty-four reported VDA events, the age of the rocks build the volcano that commonly ranges the Pliocene, Pleistocene, and Holocene. The composition material is relatively uniform, consisting of lava with basalt-andesite rock types. Scar structures are also delineated in some volcanoes. Based on these characterization results, its relationship with volcano types in Indonesia (e.g. type A, B, C) was analyzed to determine the potential for reoccurrence of VDA. Further analysis is proposed, along with a more comprehensive characterization of the VDA in Indonesia, particularly at the type A volcanoes, such as Dempo, Galunggung, Gede, Papandayan, Sundoro, and Raung.